Data Ontology - Loiko, A. I. (BNTU, 2025)
The textbook will allow students to study in depth topics related to the phi-losophy of consciousness, philosophy of artificial intelligence, philosophy of tech-nology, social philosophy, ethics and philosophy of digital law.
A textbook on the academic discipline "Philosophy and Methodology of Science" for master's students of all specialties